Esomeprazole reduces gastroesophageal reflux after beer consumption in healthy volunteers - Franke, Andreas; Hepp, Caroline Andrea; Harder, Hermann; Beglinger, Christoph; Singer, Manfred V. (Scandinavian journal of gastroenterology, 2008)
Objective. Patients with gastroesophageal reflux disease (GERD) are advised to avoid alcoholic beverages since alcohol consumption induces gastroesophageal reflux in healthy volunteers and increases it in patients with GERD. Proton-pump inhibitors (PPIs) are frequently administered for reflux symptoms but their effect on gastroesophageal reflux after alcohol consumption has not yet been fully studied. The aim of the present study was therefore to investigate the effect of esomeprazole, an S-enantiomer of omeprazole, on gastroesophageal reflux after beer consumption. Material and methods. In this placebo-controlled, double-blind, crossover study, 16 healthy male volunteers received 20 mg esomeprazole daily for one week. On day 7, in an acute experiment, the subjects then consumed 500 ml beer within 5 min. Subsequently, gastroesophageal reflux was monitored by pH-metry over a period of 3 h. In addition, gastric emptying was measured by ultrasonography and blood concentrations of ethanol, cholecystokinin and gastrin were determined. Results. Gastroesophageal reflux was significantly (p=0.001) reduced by 93% after treatment with esomeprazole (0.2%, median percentage of time pH<4) as compared to placebo (2.6%), but gastric emptying, blood ethanol and cholecystokinin concentrations were not significantly different after esomeprazole treatment. Plasma gastrin levels were significantly (p=0.0003) higher after esomeprazole (98.6±19.7 pg/ml) than after placebo (22.7±3.8 pg/ml) before beer consumption. However, there was no difference in the increase in plasma gastrin after beer consumption between the esomeprazole treatment and placebo. Conclusions. Esomeprazole significantly reduces gastroesophageal reflux after beer consumption in healthy volunteers. Gastric emptying of beer is not prolonged after treatment with esomeprazole, although compared with placebo, this PPI induced significantly higher plasma gastrin concentrations. Moderate alcohol consumption does not worsen gastroesophageal reflux when a PPI is administered.